DETERMINATION OF SATISFACTION FACTORS SERVICE QUALITY AND TRUST TOWARDS CUSTOMER LOYALTY: A CASE STUDY OF TOYOTA DEALERSHIP IN PALEMBANG - Baldi, Jolin Rusli Tee; Artina, Nyimas (Jurnal Manajemen, 2025)
This study aims to analyze the influence of customer satisfaction, service quality, and trust on customer loyalty at Toyota Dealers in Palembang. Customer loyalty is one of the complex aspects in maintaining business continuity in the highly competitive automotive industry. This study uses a quantitative method with a multiple linear regression approach to measure the influence of independent variables (customer satisfaction, service quality, and trust) on the dependent variable (customer loyalty). Primary data were collected through questionnaires distributed to 150 respondents, namely customers of Toyota Dealers in Palembang. The results of the study indicate that partially, customer satisfaction, service quality, and trust each have a significant influence on customer loyalty, with a significance value of 0.001 (<0.05). Simultaneously, the three variables also have a significant influence on customer loyalty, with a calculated F value (167.12)> F table (2.39) and a significance level of 0.001. The coefficient of determination (Adjusted R Square) of 0.628 indicates that 62.8% of the variation in customer loyalty can be explained by the three independent variables, while the remaining 37.2% is influenced by other variables outside this study. The correlation value of 0.795 indicates a strong relationship between the independent variables and customer loyalty. This study indicates that in order to increase customer loyalty, Toyota Dealers in Palembang need to focus on increasing customer satisfaction through quality after-sales service, maintaining superior service standards, and building trust through transparency and consistency of service. Further studies are recommended to explore other factors that have the potential to influence customer loyalty, such as price, promotion, and customer emotional experience.